PEMANFAATAN SERABUT KELAPA (COCO FIBER) DAN LEM KANJI (CASSAVA STARCH) MENJADI PAPAN SERAT KOMPOSIT SEBAGAI MATERIAL PENGENDALI KEBISINGAN - Waryati Waryati; Lucky Tiara Fritami; edhi Sarwono (Mulawarman University Press, 2017)
The productivity of palm plantations in Indonesia has increased so that the potential of coco such great not fully utilized, while demand for building materials noise control increases with population growth. Utilization of coconut and cassava starch into fiberboard composite is an alternative to overcome this problem. The purpose of this study is to determine variations in the optimum fiberboard composite as an absorbent material noisy as well as to determine the seven parameters (density, water content, water absorption, thickness swelling, MOE and MOR) based SNI 01-4449 - 2006 and classification of sound absorption coefficient ISO 11 654. In this research, done with laboratory scale. Sample composite board printed with the print size of 30 x 30 x 1.2 cm with a variety of coconut fiber : cassava starch (70%: 30%, 60%: 40%, 50%: 50%)The result of mechanical and physical property test of the composite board shows that the best variation is noticeable in treatment II (coco fiber ratio: 60%; cassava starch: 40%) with value of air-dry density and oven-dry density at 0,50 g/cm3, amount of water at 16,58%, permeability at 125,79%, thickness swelling at 28,28%, MOE at 1283,23 kg/cm2 and MOR at 63,82 kg/cm2. In general, the test result of the three compositions accords the SNI standard 01 – 4449 – 2006 only in terms of their density and bending strength (MOR) value. The optimum composition variation of soundproof materials is found in treatment I (coco fiber ratio: 70%; cassava starch: 30%) with maximum sound absorption coefficient of 0,49, which is categorized into Class D. Overall, the composite board has fulfilled the criteria of soundproof materials enumerated in ISO 11654. Keywords: Sound absorption coefficient, composite fiber boards, coconut fibers, mechanical properties.